A Versatile, Mild and Selective Reduction of Nitroarenes to Aminoarenes Catalyzed by CeO2 Nanoparticles with Hydrazine Hydrate. Issue 4 (25th January 2019) - Anbu, Nagaraj; Vijayan, Chellappa; Dhakshinamoorthy, Amarajothi
Abstract: A simple and convenient protocol is reported for the conversion of nitroarenes to aminoarenes by employing CeO2 nanoparticles (n‐CeO2 ) as heterogeneous solid catalysts using hydrazine hydrate as reducing agent under mild reaction conditions. A quantitative conversion of nitrobenzene is achieved using n‐CeO2 as solid catalyst with aniline selectivity to 93%. Further, this catalyst is also effectively used to transform wide range of nitroarenes to their respective aniline derivatives in higher conversions and selectivities. The reaction is found to be heterogeneous by leaching experiment and n‐CeO2 can be used for three cycles with no drop in its activity. Furthermore, the analyses of the fresh and three times used n‐CeO2 samples by powder X‐ray diffraction (XRD), UV‐Vis diffuse reflectance spectra (DRS), Fourier Transform‐Infrared Spectroscopy (FT‐IR), scanning electron microscope (SEM) and transmission electron microscope (TEM) indicate that the structural integrity, surface morphology and particle size remain unaltered during the course of the reaction. Furthermore, the valence state of Ce in n‐CeO2 is identical in the fresh and three times used samples as evidenced by Fourier Transform Raman spectroscopy. Some of the salient features of this process are operational simplicity, high conversion/selectivity, functional group tolerance, absence of noble metals/additives and reusability of the catalyst. Abstract : A simple and versatile method is reported for the reduction of series of nitroarenes to their respective aminoarenes with CeO2 nanoparticles (n‐CeO2 ) as heterogeneous solid catalysts using hydrazine hydrate as reducing agent in higher yields under mild reaction conditions. The solid catalyst is active for three cycles with no decay in its activity. Some of the salient features of this process are operational simplicity, high conversion/selectivity, functional group tolerance and absence of noble metals/additives.